2013
DOI: 10.12691/ajphr-1-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic Factors Associated with Home Delivery Assisted by Untrained Traditional Birth Attendant in Rural Bangladesh

Abstract: Delivery assisted by skilled birth attendant is recommended as a means to reduce maternal mortality. However untrained traditional birth attendant (UTBA) assisted home is very high in developing countries. The objective of this study is to assess socio-demographic determinants of UTBA assisted home delivery in rural Bangladesh. Data used in this study was obtained from women questionnaire of the 2011 Bangladesh Demographic and Health Survey (BDHS). Mothers residing in rural Bangladesh, who gave valid informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Our findings are consistent with previous studies which reported that women without exposure to information and women with at least two living children were more likely to deliver at home [30][31][32]. More importantly, our findings showed that health workers and community health volunteers are important sources for information on maternal health in rural areas and can be utilized to disseminate maternal health information in these settings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous studies which reported that women without exposure to information and women with at least two living children were more likely to deliver at home [30][31][32]. More importantly, our findings showed that health workers and community health volunteers are important sources for information on maternal health in rural areas and can be utilized to disseminate maternal health information in these settings.…”
Section: Discussionsupporting
confidence: 92%
“…The quantitative results showed that 38% of deliveries in the study area occurred at home. Although this percentage is lower than the 58-79% reported for rural women from other LMICs such as Bangladesh, Ethiopia, Tanzania and Kenya [29][30][31][32], it is a concern for the achievement of the SDGs of reducing maternal and infant mortality globally. The findings also affirm the existing documentation that some women in SSA use health facilities for ANC but go on to deliver at home where SBAs are more likely to be absent [13,32].…”
Section: Discussionmentioning
confidence: 74%
“…In the meta-analysis, Bangladesh has the second lowest OR to choose a health facility as the place of delivery than other selected countries. Due to the affordable cost and the benefit of payment negotiation, low-income families tend to undergo childbirth at home with the assistance of untrained TBAs 51. By reducing out-of-pocket expenses for institutional delivery, this behaviour can be minimised especially for the poor 52.…”
Section: Discussionmentioning
confidence: 99%
“…Women, who visit for any antenatal services, can interact with the health professional at the health facility and know possible risks of pregnancy as well as be aware of the importance of SBA during delivery [19,20].…”
Section: Discussionmentioning
confidence: 99%